Per una storia delle mostre della Fondazione Corrente (Materiali di Estetica. Terza serie, 2022)
Through an overview leaded on the Archive of the Events preserved in Fondazione Corrente, this article traces the Institution’s cultural choices following the point of view of the exhibitions’ history since 1978. It emerges a continuity between the proposal of shows dedicated to artists who were part of Corrente movement together with the desire to find in the youngest generation the fruits of those seeds of commitment in art sown before the war. At the center there is a focus on the topic of the image as an “icon”, a medium that gives the most effective and immediate communication between the sensitivity of the authors and that of the public
Keywords: History of art exhibitions; Art and politics; Corrente